Textbook in environmental science - Subramaniam, V. (New Delhi: Narosa Publishing House, 2002)
Covering all aspects of interaction of man and environment. This book addresses issues related to air, water and soil pollution and their cyclic nature introducing the reader to the diversity of flora and fauna. Global warming and climate change including the concepts are outlined in sufficient details.The subject of various environmental laws along with the policy matters that help in drafting of laws are also discussed in detail.
Include bibliographical references 231p.; Index 233-238p.
Keywords: Bio-diversity; Environmental policy; Environmental science; Global warming climate change; Geology